EFEKTIVITAS PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI SMK NURUL JADID PAITON PROBOLINGGO - Rudi Rudi; Niken Septantiningtyas (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2021)
This research was conducted to identify the implementation of online-based learning in making learning effective during the pandemic at SMK Nurul Jadid Paiton Probolinggo. This study uses a qualitative approach by collecting some data in the form of information obtained from interviews with several predetermined informants, namely the principal, vice principal, teachers, and students at SMK Nurul Jadid Paiton Probolinggo. With the hope that this research intends to describe the effectiveness of this online learning in the pandemic period which is less than two years has stopped all sectors of life. Therefore this research was conducted. And also like the implementation of online learning at SMK Nurul Jadid Paiton Probolinggo.